Direction convergence analysis of weighted rule for minor component extraction information criteria - Boyang DU; Xiangyu KONG; Xiaowei FENG (Tongxin xuebao)
The extraction of parallel minor components algorithm in directional convergence in signal feature extraction was studied.By comparing the unweighted projection approximation subspace tracking (PAST) algorithm with the weighted PAST parallel minor component extraction algorithm,the evolution method of the minor component extraction algorithm was analyzed.Theorical analysis illustrated that the weighted rule was able to guide the angle evolution between the vectors of the state matrix and minor components.Finally,Matlab simulation verifies the validity of the proposed theory.